2017
DOI: 10.1177/1756287217701861
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tolterodine on anterior segment and choroidal thickness in patients with overactive bladder syndrome

Abstract: Background: To evaluate the effects of tolterodine on anterior segment and choroidal thickness by using the Pentacam system and optical coherence tomography (OCT) (Pentacam). Methods: A total of 122 eyes of 61 patients (34 female; 27 male) were included in the study. All patients underwent a regular ocular examination and intraocular pressure measurements before and after 3 months of antimuscarinic drug tolterodine treatment, in addition, pupil diameter, anterior chamber depth, anterior chamber volume, anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Telek et al studied 61 OAB patients and the effects of three months of 1x1 daily oral administration of sustained-release tolterodine on SFCT, NCT, TCT, IOP, and PD (7). When the values before and after treatment and the p-values were compared, it was observed that SFCT (p=0.862), NCT (p=0.658), TCT (p=0.497), IOP (p=0.732), PD (p=0.711) had no differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telek et al studied 61 OAB patients and the effects of three months of 1x1 daily oral administration of sustained-release tolterodine on SFCT, NCT, TCT, IOP, and PD (7). When the values before and after treatment and the p-values were compared, it was observed that SFCT (p=0.862), NCT (p=0.658), TCT (p=0.497), IOP (p=0.732), PD (p=0.711) had no differences.…”
Section: Discussionmentioning
confidence: 99%
“…Due to various settlements of cholinergic (muscarinic) receptors (M 1 -M5) in the body, the side effects of anticholinergics emerge in accordance with this ( 6 ). These drugs can cause side effects such as dry mouth, constipation, nausea, vomiting, headache, and confusion ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%